2020
DOI: 10.1002/oby.22951
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 Rise in Younger Adults with Obesity: Visceral Adiposity Can Predict the Risk

Abstract: A concerning rise in coronavirus disease 2019 (COVID-19) cases has been recently reported, particularly in the United States. The causes of this increase are likely multifactorial and the object of an ongoing health and socioeconomic debate. However, preliminary data have indicated that the new COVID-19 cases are increasing among younger adults with obesity. Considering this recent spike, the timing of the paper by Deng et al. (1) is of particular importance. Deng et al. (1) not only confirmed that obesity is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 5 publications
0
33
0
2
Order By: Relevance
“…So far, studies investigating the role of body fat distribution on the severity and susceptibility of COVID-19 are scarce. Few observational studies investigated the association between visceral fat and COVID-19 disease severity and complications and suggested that abdominal fat is related to disease severity 29-33 . For example, in their proof-of-concept study including 30 patients with COVID-19 Petersen et al suggested that visceral fat and upper abdominal circumference specifically increased the likelihood of severe COVID-19 31 .…”
Section: Discussionmentioning
confidence: 99%
“…So far, studies investigating the role of body fat distribution on the severity and susceptibility of COVID-19 are scarce. Few observational studies investigated the association between visceral fat and COVID-19 disease severity and complications and suggested that abdominal fat is related to disease severity 29-33 . For example, in their proof-of-concept study including 30 patients with COVID-19 Petersen et al suggested that visceral fat and upper abdominal circumference specifically increased the likelihood of severe COVID-19 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Elderly patients (over the age of 60) and patients with comorbidities experience more severe symptoms of SARS-CoV-2 partially due to hyperactive chronic innate inflammatory responses as well as structural and functional changes in organs ( Frasca et al, 2017 ). Obesity increases the complications associated with the virus and aging in part due to structural/functional impairments ( Iacobellis et al, 2020a ; Malavazos et al, 2020 ) and also because visceral fat may serve as a reservoir for the virus and amplify inflammatory responses ( Ryan and Caplice, 2020 ). Obese tissues can affect the mechanics of the respiratory system by reducing the compliance and lung volumes ( Littleton, 2012 ) and pose as a risk factor for asthma ( Tashiro and Shore, 2019 ).…”
Section: Innate Immunitymentioning
confidence: 99%
“…The mechanisms may include the reprogramming of host metabolism, the exchange of microbiota components, and the adaptation of host immune and metabolic system in the presence of chronic viral infection, which produces changes in cytokine and interferons that may play a role in the development of obesity [ 193 , 194 ]. In the other way around obesity has been found to be an important risk factor for the severity of some viral infections such as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [ 195 ] and leptin has also been proposed as the possible link [ 196 ].…”
Section: Inflammation As a Mediator Of Leptin Resistance And Obesimentioning
confidence: 99%